Study of Some Durability Properties of Self-compacting Concrete Containing Waste Polyethylene Terephthalate - Majid, Marwah; Mohammed, Mahmoud (Anbar Journal of Engineering Sciences, 2023)
This study aims to investigate the durability properties and microstructural changes of self-compacting concrete (SCC) incorporating waste polyethylene terephthalate (PET) as fibers and as fine aggregate replacement. This is after exposed to saline environment (Alkalies, Sulphates, and Chlorides). PET effect into two forms was also evaluated for routine rheological properties of SCC and mechanical strength before and after exposure to sulphate salt. Five proportions of each form of PET incorporation in SCC mixtures were utilized. The volume fractions considered for PET as fibers were (0.25, 0.5, 0.75, 1.0, and 1.25)% by volume, with aspect ratio of 28%, and (2, 4, 6, 8, and 10)% by volume for fine aggregate replacements. Results indicated that the inclusion of PET adversely affected fresh propertis especially high proportions of PET as fine aggregate. Alkali silica reaction (ASR) outcomes illustrated an enhancement in the mix containing PET fibers, while fine-PET mix was slightly enhanced. Magnesium sulphate reduced mass and compressive strength of all mixes in percentages ranging from (0.18-0.90) % for mass loss and from (0.47-55.13) % for compressive strength loss. Ultrasonic pulse velocity (UPV) and dynamic modulus of elasticity (Ed) increased due to the sulphate impact except for M0.5 and M10 which decreased in both tests. Chloride's theoretical and modelled results illustrated higher diffusion coefficients and lower surface chloride content of fiber-PET mixes as compared to fine-PET mixes. The predicted SCC cover depths for fiber-PET mixes were lower than those predicted for fine-PET mixes for 20 and 50 years of service life design.